ANALISA KEPUTUSAN PEMBELIAN KONSUMEN DI INSTAGRAM - Julius Afriyanto, (2020)
This is a research about consumer's purchase intention on social media instagram. This is a quantitative research with aims to determine the effect of quality product, word of mouth through brand image as mediator variable on consumer's purchase intention on social media instagram with millenial's generation as population. The sample size for this research is 75 repondents, with non probability sampling, purposive sampling as the method. The data collection was carried out through quistionnaires of google forms. The analysis technique used is PLS (Partial Least Square) analysis with smartPLS 3.0 software. The result of this research indicate that (1) quality product significantly influence brand image. (2) quality product significantly influence consumer's purchase intention. (3) word of mouth significantly influence brand image. (4) word of mouth can influence consumer's purchase intention but not significant. (5) brand image can influence consumer's purchase intention but not significant